Sign based system for controlling devices, appliances and the like. - Noordin, Nor Kamariah; Ng, Chee Kyun; Mohd Ali, Borhanuddin; Jin, Hui Chong; Ng, Wei Lun (2009)

(untitled)
This invention presents a simple sign based automating controller for various household appliances. It consists of three main components: the sign based recognition system, the household appliances sensing system, and the data center system for data collection and processing. A flex sensor is attached to each finger in a data glove. The attached microcontroller in the data glove receives the sensors signal data processing (DSP). Analyzed data are transmitted to the data center in either two ways, wireless or wired transmission. The data center matches the received glove data with associated command data using matching algorithm. When the data is matched, the command data will be sent to the related household appliance device through wireless or wired transmission.